An experimental study of the antioxidant complex for the prevention of adhesions in the abdominal cavity - М. Yu. Grischenko; А. V. Potapov; Ye. Yu. Varakuta; S. V. Logvinov; M. B. Plotnikov; L. R. Mustafina; V. I. Tikhonov; D. A. Shkatov (Бюллетень сибирской медицины, 2012)
Antioxidant complex under the experimental conditions in male rats of Wistar effectively reduces the severity of adhesions in the abdominal cavity. The morphological study showed that the mechanism of action of antioxidant complex is aimed at reducing inflammation, edema and improvement of microcirculation in the zone of damage.